2021
DOI: 10.1111/jocn.15918
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mental health symptoms and insomnia levels of intensive care nurses during the COVID‐19 pandemic with a structural equation model

Abstract: Background: Faced with this critical situation and directly involved in the treatment and care of COVID-19 patients, front-line healthcare workers are at high risk in terms of mental health symptoms. Aims and Objectives:To determine the stress, anxiety, depression, and insomnia levels of intensive care nurses during the pandemic with a structural equation model. Design:A multi-site survey study. Methods:The study was performed with 194 nurses working in the intensive care units of five hospitals in Istanbul in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…The total scores ranged from 3 to 6. Most of the studies (114) [ [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], [ [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], [ [63] , [64] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , [75] , [76] , [77] ], [ [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , 91 , [93] , [94] , [95] , [96] , [97] , [98] , [99] ], [ [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [113] , …”
Section: Resultsunclassified
“…The total scores ranged from 3 to 6. Most of the studies (114) [ [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], [ [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], [ [63] , [64] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , [75] , [76] , [77] ], [ [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , 91 , [93] , [94] , [95] , [96] , [97] , [98] , [99] ], [ [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [113] , …”
Section: Resultsunclassified
“…In addition, they were in a state of high arousal more potentially, which will seriously affect sleep (49). Kandemir et al investigated 192 frontline HCWs in the fight against the epidemic and found that approximately 80.41% of them had sleep disturbance (69). Therefore, psychological problems were more likely to occur when sleep disturbance occurred.…”
Section: Association Between Sleep Disturbance and Mental Healthmentioning
confidence: 99%
“…Nurses working in the COVID-19 intensive care units during the pandemic period experience many problems, such as stress, sleep problems, anxiety, depression, and burnout ( Kandemir et al, 2022 ; Azoulay et al, 2020 ). According to the results obtained in our study, 53.0% of the nurses were found to have anxiety and 76.6% to have depression.…”
Section: Discussionmentioning
confidence: 99%